Intracellular Bacterial Symbionts in Corals: Challenges and Future Directions - Justin Maire; Linda L. Blackall; Madeleine J. H. van Oppen (Microorganisms, 2021)
Corals are the main primary producers of coral reefs and build the three-dimensional reef structure that provides habitat to more than 25% of all marine eukaryotes. They harbor a complex consortium of microorganisms, including bacteria, archaea, fungi, viruses, and protists, which they rely on for their survival. The symbiosis between corals and bacteria is poorly studied, and their symbiotic relationships with intracellular bacteria are only just beginning to be acknowledged. In this review, we emphasize the importance of characterizing intracellular bacteria associated with corals and explore how successful approaches used to study such microorganisms in other systems could be adapted for research on corals. We propose a framework for the description, identification, and functional characterization of coral-associated intracellular bacterial symbionts. Finally, we highlight the possible value of intracellular bacteria in microbiome manipulation and mitigating coral bleaching.